Vaccinal Prevention of Lower Respiratory Tract Pneumococcal Disease in Adults Without Immunosuppression - I. A. Guchev (Антибиотики и Химиотерапия)
Community-acquired pneumonia (CAP) remains one of the major healthcare problems globally. Pneumococcal disease is the leading cause of deaths among vaccine preventable diseases in children and adults. Plain polysaccharide vaccine PPSV-23 and conjugated pneumococcal polysaccharide vaccine PCV-13 are widely used to prevent pneumococcal disease and CAP in adults without immunosuppression. The review concerns the results of trials and meta-analysis of PPSV-23 and PCV-13 effectiveness in invasive pneumococcal disease (IPD) and CAP prevention in immunocompetent adults. More and more expert immunization committees in different countries are taking into consideration uncertain effectiveness of PPSV-23 in CAP prevention in immunocompetent adults, and recommend the PCV-13 priority use for mass immunization campaigns in high-risk groups and elder population. Since the Russian Federation has started the PCV-13 vaccination campaign for early childhood only at the end of 2014, the anticipated serotype replacement should not be taken into consideration at the moment across all the age groups, and therefore the risk and age based approach to adult vaccination should be used with the PCV-13 priority.